Analysis of Predisposing, Reinforcing, and Enabling Factors on Human Papilloma Virus (HPV) Vaccination Behavior Based on Green's Theory - Linda Juwita; Ninda Ayu Prabasari; Steven Aldo Marcello (GLOBAL HEALTH SCIENCE GROUP, 2025)
Women exposed to HPV are at a higher risk of developing cervical cancer. One preventive measure is HPV vaccination, which can be administered starting at the age of >9 years. However, the motivation, willingness, and acceptance of HPV vaccination among adolescents remain relatively low. This study aims to analyze the relationship between predisposing, reinforcing, and enabling factors influencing HPV vaccination behavior in adolescent girls based on Green's theory. This research is a descriptive analytic study using a cross-sectional approach. The population consists of female adolescents from SMA Pembangunan Jaya 2. The sampling technique used is purposive sampling, targeting participants who meet the inclusion criteria. The independent variables include predisposing factors (knowledge, attitude), reinforcing factors (information sources, costs), and enabling factors (family support, peer support). The dependent variable is HPV vaccination behavior. Data were analyzed using bivariate statistical analysis with the Chi-Square test. Statistical tests on predisposing and reinforcing factors using Chi-Square revealed that knowledge (p-value: 0.097 > 0.05), attitude (p-value: 0.084 > 0.05), information sources (p-value: 0.285 > 0.05), and costs (p-value: 0.981 > 0.05). For enabling factors, parental support (p-value: 0.001 < 0.05) and peer support (p-value: 0.021 < 0.05). Predisposing and reinforcing factors do not have a significant relationship with HPV vaccination behavior, while enabling factors have a significant relationship with HPV vaccination behavior.